Business AI for Oil and Gas: Unlocking Efficiency Across the Value Chain - Rajeshwar Guggilla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative impact of artificial intelligence (AI) on the oil and gas industry, focusing on its applications across the value chain from exploration to end-user delivery. It examines the potential of AI, particularly generative AI, to optimize various aspects of the sector, including exploration, development, production, transportation, refining, and sales. The article discusses specific AI applications in refinery processes. It highlights the significant benefits of AI implementation, such as improved operational efficiency, reduced downtime, enhanced decision-making, cost reduction, and increased safety. Drawing on industry studies and research, the article presents quantitative data on the potential cost savings, productivity improvements, and value creation that AI technologies can bring to the oil and gas sector.